Effect of Intensive Blood Pressure Lowering on the Risk of Incident Silent Myocardial Infarction: A Post Hoc Analysis of a Randomized Controlled Trial - Richard Kazibwe; Muhammad Imtiaz Ahmad; Sanjay Singh; Lin Y. Chen; Elsayed Z. Soliman (Annals of Noninvasive Electrocardiology)
ABSTRACT Background Silent myocardial infarction (SMI) frequently goes undetected, yet it is associated with increased cardiovascular morbidity and mortality. The impact of intensive systolic blood pressure (SBP) lowering on the risk of SMI in those with hypertension remains uncertain. Methods In this post hoc analysis of the Systolic Blood Pressure Intervention Trial (SPRINT), participants with serial electrocardiograms (ECGs) during the trial were included. SPRINT investigated the benefit of intensive SBP lowering, aiming for < 120 mmHg compared to the standard SBP goal of < 140 mmHg. Incident SMI was defined as evidence of new MI on an ECG without adjudicated recognized myocardial infarction (RMI). Results During a median follow‐up of 3.9 years, a total of 234 MI events (55 SMI and 179 RMI) occurred. Intensive, compared to standard, SBP lowering resulted in a lower rate of SMI (incidence rate 1.1 vs. 2.3 cases per 1000 person‐years, respectively; HR [95% CI]: 0.48 [0.27–0.84]). Similarly, intensive, compared to standard, BP lowering reduced the risk of RMI (incidence rate 4.6 vs. 6.5 cases per 1000 person‐years, respectively; HR [95% CI]: 0.71 [0.52–0.95]). No significant differences were noted between the strength of the association of intensive BP control on lowering the risk of SMI and RMI (p‐value for HR differences = 0.23). Conclusions This study shows that in adults with hypertension, the benefits of intensive SBP lowering, compared with standard BP lowering, go beyond the prevention of RMI to include the prevention of SMI. Trial Registration ClinicalTrials.gov Identifier: NCT01206062.